2021
DOI: 10.1186/s41256-021-00190-7
|View full text |Cite
|
Sign up to set email alerts
|

Health financing for universal health coverage in Sub-Saharan Africa: a systematic review

Abstract: Background Universal health coverage (UHC) embedded within the United Nations Sustainable Development Goals, is defined by the World Health Organization as all individuals having access to required health services, of sufficient quality, without suffering financial hardship. Effective strategies for financing healthcare are critical in achieving this goal yet remain a challenge in Sub-Saharan Africa (SSA). This systematic review aims to determine reported health financing mechanisms in SSA with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
86
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(104 citation statements)
references
References 40 publications
1
86
0
1
Order By: Relevance
“…Thus, the risk of transmission of the virus to the elderly in these homes is magnified once a household inhabitant contracts the disease. Furthermore, lower income households are less likely to have easy access to health facilities for care in countries that rely more on out-of-pocket payment for care, such as Nigeria and Ethiopia (Ifeagwu et al, 2021 ). This can influence the decision to present in health facilities for care and the delay can further result in exposure to other members of the household and community, with eventually poor outcomes among those that might contract the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the risk of transmission of the virus to the elderly in these homes is magnified once a household inhabitant contracts the disease. Furthermore, lower income households are less likely to have easy access to health facilities for care in countries that rely more on out-of-pocket payment for care, such as Nigeria and Ethiopia (Ifeagwu et al, 2021 ). This can influence the decision to present in health facilities for care and the delay can further result in exposure to other members of the household and community, with eventually poor outcomes among those that might contract the disease.…”
Section: Discussionmentioning
confidence: 99%
“…The deficits in managerial awareness and capacity, coupled with their exclusion from engagement of policy formulation and rollout, is contradictory to the apparent purpose of the NHI Bill to empower the DHS to assume responsibility for the needs of predefined municipal areas. Joint learning from Asian [ 14 ], Latin American [ 12 ] and African [ 13 , 23 , 24 ] regions has shown that incomplete operationalization of the DHS hinders UHC implementation strategies [ 10 ] and leads to wasteful expenditure. Conversely, success stories from countries such as Cuba [ 12 ], Thailand and Indonesia [ 7 ] show that UHC can be successfully implemented in the face of fiscal austerity, when sustained investment in decentralised governance strategies that enabled CUPs and strategic purchasing.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, success stories from countries such as Cuba [ 12 ], Thailand and Indonesia [ 7 ] show that UHC can be successfully implemented in the face of fiscal austerity, when sustained investment in decentralised governance strategies that enabled CUPs and strategic purchasing. Similarly, several African countries such as Uganda and Ghana have effectively used decentralised governance strategies to facilitate UHC success [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior to the start of the COVID-19 pandemic, health systems in Africa have been strained from the burden of historic underinvestment (9,10). The attendant weaknesses meant that countries were not on track to achieve global human health development goals -including the health-related Sustainable Development Goals (11).…”
Section: Introductionmentioning
confidence: 99%